Bacterial meningtis: a five year (2001-2005) retrospective study at University Malaya Medical Centre (UMMC), Kuala Lumpur, Malaysia - Erleena Nur, H.; Jamaiah, I.; Rohela, M.; Nissapatorn, V. (SEAMEO Regional Tropical Medicine and Public Health Network, 2008)
This was a five year (2001-2005) retrospective study of bacterial meningitis in patients admitted to UMMC. A total of 47 cases were analyzed. Chinese was the most common ethnic group (41), followed by Malays (36) and Indians (23). The majority of cases (60) were within the 0-9 year old age group. Within this age group, the majority (93) was less than 5 years old. For all races, males were more commonly infected (62) than females. The most common presenting complaints were fever (83), vomiting (25.5), headache (23), seizures (23), and loss of consciousness (11). On admission, 23 had neck stiffness. Cerebrospinal fluid (CSF) cultures were positive for Streptococcus pneumoniae (23), Haemophilus influenzae (15), Escherichia coli (8.5), Neisseria meningitidis (4) and Streptococcus spp (2). CSF investigations were not done on 47 of cases due to contraindications. The most common complication was subdural effusions (15), followed by cerebral edema (8.5), epilepsy (8.5) and hydrocephalus (6). The antibiotic sensitivity tests done showed that all the three major organisms were 100 sensitive to ceftriaxone. 5. pneumoniae was 100 sensitive to penicillin and H. influenzae was 90 sensitive to penicillin and ampicillin. The mortality rate was 15.